Organisation of powers between Region and municipalities in Brussels: going beyond the antagonism of the “Tina” and “Nimby” approaches - Nicolas Lagasse (Brussels Studies)
Does the “big city” project take place via the suppression of municipalities and the drastic reduction in their powers? There is a heated debate between “regionalists” and “municipalists”. A legal analysis provides lines of thought to stop this “trench war”. The Constitution and the European Charter of Local Self-Government provide a framework for reflection. The law does not impose or exclude any scenario, but forces the legislator to question the possibility of synergetic cooperation between the Region and the municipalities in terms of the principles of subsidiarity and proportionality. Based on this, four questions are asked in the article. Does the Region make full use of its capacity for cohesion and coordination? Is the municipal institution organised in the most efficient way? Have all of the methods for dialogue and synergy been mobilised? Should inter-municipal collaborations not be revised in view of improving the quality of service at a lower cost? This reflection opens the way to rationalising the organisation of institutions and promoting the methods of cooperation.